Deteksi faktor risiko penyakit infeksi saluran pernafasan dan lingkungan pada anak suku Kamoro, Mimika, Papua : Indonesia - Lusiyana, Novyan (Jurnal Abdimas Madani dan Lestari (JAMALI), 2025)
Children are individuals who are vulnerable to infectious diseases. This disease can be influenced by various factors such as knowledge, behavior and environment. Identification of risk factors can determine the right intervention method. This community service aims to identify potential infectious diseases, their risk factors and evaluate the intervention methods given to children to prevent infectious diseases. This activity was carried out in the Kamoro tribal village, Mimika Papua. The activity was carried out in March 2024 targeting pre-school children and school children. This service consists of 3 stages, namely which are health examination, environmental surveys and education on infectious disease prevention behavior. Health examinations are carried out to identify ear, respiratory tract, digestive tract and skin diseases. Environmental identification is carried out by surveying the village environment and education is carried out through counseling, questions and answers and simulations. The results of this service show that most Kamoro children experience upper respiratory tract infections (URTI) (70.37%), with risky environmental factors in the form of lack of sanitation facilities, clean water and puddles. Education on infectious disease prevention behavior shows that the question-and-answer method is less than optimal, but the simulation method is easier for Kamoro children to understand. It can be concluded that ISPA is an infectious disease that is often suffered by Kamoro children with risk factors such as type of house, availability of clean water, toilets and puddles. Prevention education with simulation methods is more appropriate for learning disease prevention.